Providing person-centered palliative care in conflict-affected populations in the Middle East: What matters to patients with advanced cancer and families including refugees? - Guo, Ping; Alajarmeh, Sawsan; Alarjeh, Ghadeer; Alrjoub, Waleed; Al-Essa, Ayman; Abusalem, Lana; Giusti, Alessandra; Mansour, Asem H.; Sullivan, Richard; Shamieh, Omar; Harding, Richard (Frontiers in Oncology, 2023)
Introduction Universal health coverage highlights palliative care as an essential component of health services. However, it is unclear what constitutes person-centered care in populations affected by conflict, as they may have specific concerns in the dimensions of physical, emotional, social, and spiritual wellbeing. This study aimed to identify what matters to patients with advanced cancer and family caregivers in Jordan including refugees, to inform appropriate person-centered assessment and palliative care in conflict-affected populations. Methods Cross-sectional face-to-face, semi-structured interviews were conducted at two sites in Amman. Adult patients with advanced cancer and family caregivers were purposively sampled to maximize diversity and representation. Interviews were digitally audio recorded, anonymized, and transcribed verbatim for thematic analysis. Findings Four themes were generated from 50 patients (22 refugees; 28 Jordanians) and 20 caregivers (7 refugees; 13 Jordanians). (1) Information, communication, and decision-making. Truth-telling and full disclosure from clinicians was valued, and participants expressed concerns that information was not shared in case patients would disengage with treatment. (2) Priorities and concerns for care and support. Participants’ top priority remained cure and recovery (which was viewed as possible). Other priorities included returning to their “normal” life and their “own” country, and to continue contributing to their family. (3) Role of spirituality and Islam. Most participants had strong faith in God and felt that having faith could comfort them. For refugees whose social network was fractured due to being away from home country, prayer and Quran reading became particularly important. (4) Unmet support needs of family caregivers. Family caregivers were affected physically and emotionally by worrying about and caring for the patients. They needed support and training, but often could not access this. Discussion Truth-telling is highly valued and essential to achieving person-centered care and informed decision-making. This study also reveals specific concerns in conflict-affected populations, reflecting the experience of prior losses and fracturing of existing social networks and support. The role of religion is crucial in supporting refugee communities, and consideration should be paid to the needs of patients/caregivers when caring for someone at home without access to their communities of origin and the support they accessed.